The development of generosity and moral cognition across five cultures. Issue 4 (4th May 2016) - Cowell, Jason M.; Lee, Kang; Malcolm‐Smith, Susan; Selcuk, Bilge; Zhou, Xinyue; Decety, Jean
Abstract: Morality is an evolved aspect of human nature, yet is heavily influenced by cultural environment. This developmental study adopted an integrative approach by combining measures of socioeconomic status (SES), executive function, affective sharing, empathic concern, theory of mind, and moral judgment in predicting sharing behavior in children (N = 999) from the age of 5 to 12 in five large‐scale societies: Canada, China, Turkey, South Africa, and the USA. Results demonstrate that age, gender, SES, culture, and social cognitive mechanisms explain over 20% of the variance worldwide in children's resource allocation. These findings are discussed in reference to standard cultural comparisons (individualist/collectivist), as well as the degree of market integration, and highlight continuities and discontinuities in children's generosity across urban contexts. Abstract : This developmental study combined measures of socioeconomic status (SES), executive function, affective sharing, empathic concern, theory of mind, and moral judgment in predicting sharing behavior in children (N = 999) from the age of 5 to 12 in five large‐scale societies. Results demonstrate that age, gender, SES, culture, and social cognitive mechanisms explain over 20% of the variance worldwide in children's resource allocation, highlighting continuities and discontinuities in children's generosity across urban contexts.